Environmental aspects of use of recycled carbon fibre composites in automotive applications - Meng, Fanran; McKechnie, Jon; Turner, Thomas; Wong, Kok H.; Pickering, Stephen J. (ACS Publications, 2017)
The high cost and energy intensity of virgin carbon fibre manufacture provides an opportunity to recover substantial value from carbon fibre reinforced plastic wastes. In this study, we assess the life cycle environmental implications of recovering carbon fibre and producing composite materials as substitutes for conventional and proposed lightweight materials in automotive applications (e.g., steel, aluminium, virgin carbon fibre). Key parameters for the recycled carbon fibre materials, including fibre volume fraction and fibre alignment, are investigated to identify beneficial uses of recycled carbon fibre in the automotive sector. Recycled carbon fibre components can achieve the lowest life cycle environmental impacts of all materials considered, although the actual impact is highly dependent on the design criteria (λ value) of the specific component. Low production impacts associated with recycled carbon fibre components are observed relative to lightweight competitor materials (e.g., aluminium, virgin carbon fibre reinforced plastic). In addition, recycled carbon fibre components have low in-use energy use due to mass reductions and associated reduction in mass-induced fuel consumption. The results demonstrate environmental feasibility of the CFRP recycling materials, supporting the emerging commercialisation of CF recycling technologies and identifying significant potential market opportunities in the automotive sector.